2021
DOI: 10.1007/s10552-021-01433-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of breast cancer in relation to dietary intake of selenium and serum selenium as a marker of dietary intake: a prospective cohort study within The Malmö Diet and Cancer Study

Abstract: Purpose Selenium has been suggested to be protective against breast cancer, but the evidence remains inconclusive. Hence, it is important to further examine the potential protective effect. This prospective cohort study investigates pre-diagnostic selenium intake in relation to breast cancer risk. In addition, we analyze serum selenium as a marker of dietary intake. Methods This study includes 17,035 women in the Malmö Diet and Cancer cohort. Dietary asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(89 reference statements)
2
6
0
Order By: Relevance
“…A protective effect of intermediate or high selenium intake was seen among women carrying C/T or T/T alleles in a stepwise fashion, compared to women with the C/C allele. The overall effect of selenium intake and serum selenium has previously been reported for this cohort, and we found no further interactions with the other four SNPs investigated [18,23]. We found no effect on breast cancer risk when using genetically elevated selenium levels as exposure measurement.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A protective effect of intermediate or high selenium intake was seen among women carrying C/T or T/T alleles in a stepwise fashion, compared to women with the C/C allele. The overall effect of selenium intake and serum selenium has previously been reported for this cohort, and we found no further interactions with the other four SNPs investigated [18,23]. We found no effect on breast cancer risk when using genetically elevated selenium levels as exposure measurement.…”
Section: Discussionsupporting
confidence: 75%
“…Descriptive statistics for tertiles of allele score in relation to established risk factors for breast cancer were investigated in a cross table. Descriptive statistics for dietary selenium intake and serum selenium have been published previously for this cohort [18,23].…”
Section: Discussionmentioning
confidence: 99%
“…Mainly due to the function of several of the selenoproteins controlling redox status, antioxidative reactions and protective pathways, a beneficial role of Se for maintaining health and avoiding disease has been discussed since more than 40 years [ 6 , 7 ]. While no consistent results were obtained for cancer incidence [ [8] , [9] , [10] ], several independent studies reported dose-dependent associations of low Se status with poor prognosis. An inverse association of Se status with cancer-prognosis is described for multiple cancer sites, including laryngeal [ 11 ], colorectal [ 12 , 13 ], lung [ 13 , 14 ], prostate [ 13 ], skin [ 15 ], and breast [ [16] , [17] , [18] , [19] , [20] ], and it was also observed in large-scale studies assessing all-cancer mortality including NHNAES III [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum was extracted from non-fasting participants at baseline and stored at −80 • C until use. The analyses of serum zinc, selenium and phosphorus are described in more detail in three previous studies [4,21,23]. Briefly, analyses of zinc and selenium were conducted with an amount of 0.15 mL serum using inductively coupled plasma sector-field mass spectrometry.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…The baseline examinations took place between 1991 and 1996 and included dietary assessment, blood samples and a self-administered questionnaire with questions regarding factors such as lifestyle, medical history, reproductive factors and socioeconomic status. The design and baseline examinations of the MDCS have been described in more detail elsewhere [18][19][20][21].…”
Section: The Malmö Diet and Cancer Studymentioning
confidence: 99%